Youth participatory arts, learning and social transformation : engaging people, place and context with Big hART - Wright, Peter R. (College teacher); Down, Barry, 1953- (Brill, Sense, 2021)
"This book provides a unique insiders account of the work of Big hART, one of Australia's leading participatory arts organisations. Founded on the values of social justice, creativity and transformation Big hART seeks to mobilise a range of community resources including young people, elders, artists, and community activists to produce high quality public performances of merit and social worth. Located in diverse geographic, social and cultural settings across Australia's vast landscape, these creative works generate intergenerational understandings of the cultural processes of individual and collective transformation strengthening capabilities, identity, and connected belonging. This book documents a series of powerful stories that illuminate the ideological, artistic and cultural pathways and learnings gifted by the generosity of participants themselves"--